2015
DOI: 10.1002/lsm.22310
|View full text |Cite
|
Sign up to set email alerts
|

1064 nm long‐pulsed Nd:YAG laser treatment of basal cell carcinoma

Abstract: The 1064 nm long-pulsed Nd:YAG laser may offer a safe alternative for treating BCC off the face. A larger study is highly warranted to confirm these preliminary results. Lasers Surg. Med. 47:106-110, 2015. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 18 publications
1
48
1
9
Order By: Relevance
“…This study demonstrated a 92% histologic clearance rate (12 of 13 BCC tumors) after one treatment, while 100% clearance rates were achieved when stratified to those treated with fluences of 120 J/cm 2 (10 of 10 BCC tumors). Treatments were tolerated without any significant adverse events .…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated a 92% histologic clearance rate (12 of 13 BCC tumors) after one treatment, while 100% clearance rates were achieved when stratified to those treated with fluences of 120 J/cm 2 (10 of 10 BCC tumors). Treatments were tolerated without any significant adverse events .…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated complete histologic clearance after 1 treatment in 92% of the BCC tumors, and at higher fluences, the study was able to demonstrate 100% histologic clearance after 1 treatment. 30 No significant adverse events were noted, including scarring.…”
Section: Laser Therapy For the Treatment Of Basal Cell Carcinomasmentioning
confidence: 94%
“…Lasers such as the long-pulsed 1,064 nm neodymium-doped yttrium aluminum garnet (Nd: YAG) and 755 nm Alexandrite lasers penetrate 50% to 75% deeper into the skin than the PDL. 13,26,2830 Additionally, the conversion of oxyhemoglobin to methemoglobin after irradiation with PDL creates a second target chromophore for the Nd:YAG laser if PDL is used first followed by Nd:YAG. However, these lasers have a much lower absorption coefficient in blood than in PDL, requiring higher fluences and increasing the risk of adverse effects.…”
Section: Laser Therapy For the Treatment Of Basal Cell Carcinomasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the occurrence of persistent dyspigmentation still limits the therapy success in terms of an excellent cosmetic outcome. Ortiz et al [27] put forward that the 1064-nm long-pulsed Nd:YAG laser could offer a safe alternative for treating BCC outside of the face with a prospective, non-randomized, open-label clinical trial. A larger study is required to confirm these preliminary results.…”
Section: Light and Lasers On Skin Cancermentioning
confidence: 98%